A fractional number based labeling scheme for dynamic XML updating - Nooshabadi, Meghdad Mirabi; Ibrahim, Hamidah; Fathi, Leila; Mamat, Ali; Udzir, Nur Izura (Universiti Utara Malaysia Press, 2011)
Recently, XML query processing based on labeling schemes has been proposed. Based on labeling schemes, the structural relationship between XML nodes can be determined quickly without the need of accessing the XML document. However, labeling schemes have to re-label the pre-existing nodes or re-calculate the label values when a new node is inserted into the XML document during the update process. In this paper, we propose a novel labeling scheme based on fractional numbers. The key feature of fractional numbers is that infinite number of fractional numbers can be inserted between any two unequal fractional numbers. Therefore, the problem of re-labeling the pre-existing nodes during the XML updating can be solved if the XML nodes are label by the fractional numbers.